Pengaruh Disiplin Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada J&T Express Drop Center 21 Depok - Agustina Dewi Srihatin; Retno Japanis Permatasari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to determine the effect of discipline and physical work environment on employee performance at J&T Express Drop Center 21 Depok. The method used is quantitative associative. The study population was 62 people and all of them were sampled in this study. The data analysis techniques used in this study are instrument test, classical assumption test, regression test, correlation coefficient test, determination coefficient test and hypothesis testing. The results showed that discipline has a positive and significant effect on employee performance, this is evidenced by the value of t count> t table (5.424> 2.000) and reinforced by the sig value <0.05 (0.000 <0.05) so that H0 is rejected and H1 is accepted, so there is a positive and significant influence between discipline on employee performance. The physical work environment has a positive and significant effect on employee performance, this is evidenced by the value of t count> t table (3.033> 2.000) and strengthened by the sig value <0.05 (0.004 <0.05) so that H0 is rejected and H2 is accepted, Then there is a positive and significant influence between the physical work environment on employee performance discipline and work environment have a positive and significant effect on employee performance, this is evidenced by t count> t table (144.224> 3.15) and strengthened by sig value <0.05 (0.00 <0.05, there is a positive and significant influence between discipline and physical work environment simultaneously on employee performance.